Leadership in Action: An Evolutionary View: What Followers Want from Their Leaders - Winsborough, David; Kaiser, Robert; Hogan, Robert (Center for Creative Leadership, 2009)
A look into the very distant past of human existence shows that some conditions are more conducive to leadership than others and that followers naturally prefer specific forms of leadership and resist other forms. By understanding and acting on the three fundamental individual needs that result from group living and the three tough problems faced by ancient tribes, leaders can better connect with their followers.